In non-melanoma skin cancer, prognostic factors and the role of adjuvant radiation therapy: Retrospective, a single-center experience (Annals of Medical Research, 2023)
Aim: Non-melanoma skin cancer (NMSC) is the most prevalent malignancy worldwide, with basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) representing the most common types of NMSC. In this retrospective analysis, patients with NMSC who had adjuvant radiotherapy (RT) had their treatment results and prognostic variables evaluated.Materials and Methods: A total of 115 patients with NMSC who had adjuvant RT in our clinic during January 2006 and September 2021 were assessed. The average age was 74 years, and the male to female ratio was 1.95:1. (range: 25–95). The most often diagnosed kind of NMSC was SCC (93%, n=107), preceded by BCC (7%, n=8). The extremities (17.4%, n=20), the trunk (1.7%, n=2), and the head and neck area (80.9%, n=93) were where the bulk of NMSC lesions were discovered.Results: The mean follow-up period was 60.7 months (the range was 4.2–194.7); metastases were found in six patients (5.2%), and locoregional recurrence was identified in 24 patients (20.8%). The 3- and 5-year total survival percentages were 71.2% and 59.3%, respectively, and the median overall survival (OS) time was 87.1 months. Tumor size and surgical margin status were linked to a worse OS in multivariate analysis of prognostic variables (hazard rate [HR]=3.0, 95% confidence interval [CI]: 1.8-5.2; p=0,001 and HR=2.4, 95% CI: 1.4-4.1; P=0,002, respectively).Conclusion: Postoperative RT is an efficient, acceptable therapeutic option for NMSC in high-risk individuals. Our results suggest that surgical margin and tumor size were independent predictors of OS in NMSC patients; nevertheless, future studies including more patients are required to corroborate these results.
Keywords: Skin cancer; Squamous cell carcinoma; Basal cell carcinoma; Radiotherapy